Seatbelt: A Double-Edged Sword - P. Raychaudhuri; N. K. Cheung; C. Bendinelli; M. Puvaneswary; R. Ferch; Rajendra Kumar (Case Reports in Pediatrics)
Intra-abdominal vascular injury due to blunt trauma is unusual in children. Due to its rarity, detailed reports dealing with its management are scarce in paediatric literature. Diagnosis of these injuries is challenging, and a high degree of awareness is necessary for rapid identification and treatment of these injuries. We report the case of a child with seatbelt sign and mesenteric vein injury due to blunt trauma to the abdomen during a motor vehicle accident where the seatbelt was incorrectly placed. She also sustained cervical vertebral injury. The pattern of injuries in children in these situations may differ from that found in adults. While seatbelts have undoubtedly saved many lives, awareness about correct placement of these restraints is extremely necessary.